Thrombosed Fetal Dural Sinus Malformation: A Case Report - Tayseer Al Muteri; Muna Al Rawahi; Felipe Moretti (Journal of Pharmacy and Bioallied Sciences)
Background: Fetal dural venous sinus thrombosis is an uncommon disorder in which a blood clot forms in the developing fetus’s dural venous sinuses. A detailed ultrasound examination, including neurosonography, and color Doppler are usually used to identify it, and fetal brain magnetic resonance imaging (MRI) is used to confirm the diagnosis. Although few case reports exist, the incidence of fetal occurrence remains unknown. Case Description: A 25-year-old woman, primigravida, with no comorbidities at 20 weeks and 1 day, underwent a detailed ultrasound followed by MRI. The imaging revealed a triangular extra-axial expansile lesion measuring 1.6cm AP × 3 craniocauded × 2.6cm transverse diameter. - The lesion was located at the torcula, at the confluence of the transverse sinuses, extending towards the posterior aspect of the left transverse sinus. This extension caused flattening of the posterior portion of the cisterna magna and the left posterior aspect of the cerebellum. The size of the intracranial mass increased. Fetal and parental investigations failed to find any underlying cause. The patient had a spontaneous vaginal birth at 38 weeks. A postnatal diagnosis of thrombosis in the sinus was confirmed by MRI and venography. No brain damage or hydrocephalus was noted, and the neurological outcome was normal at 9 months of age. Conclusion: Fetal intracranial thrombosis can result from dural sinus abnormalities. When dural sinus malformation (DSM) is detected in prenatal imaging, timely fetal MRI is recommended to help diagnose dural sinus abnormalities, identify intracranial complications, and determine perinatal plan and management options.